Gastro-Intestinal Stromal Tumour presenting as Gastroduodenal Intussusception (Nepalese Journal of Radiology, 2014)
Gastrointestinal stromal tumours (GISTs), are relatively common tumours of the gastrointestinal tract, most commonly found in the stomach. Previously they were termed as leiomyomas and leiomyosarcomas. Clinically, they are asymptomatic but may cause abdominal pain or bleeding from ulceration of the overlying mucosa. We present a case of gastroduodenal intussusception secondary to large gastric stromal tumour in a 50 year old male, which presented with intermittent abdominal pain and gastric outlet obstruction. Pre-operative diagnosis was made on abdominal CT and confirmed at laparotomy. DOI: http://dx.doi.org/10.3126/njr.v4i1.11573 Nepalese Journal of Radiology, Vol.4(1) 2014: 71-75